A 54‐kDa short variant of DHX33 functions in regulating mRNA translation. Issue 9 (26th January 2019) - Su, Dan; Yuan, Baolei; Su, Chenjing; Zhang, Yandong
Abstract: DEAH box protein DHX33 has been found to be necessary for cell proliferation and early development of multicellular organisms. It plays diverse roles in regulating gene transcription, ribosome RNA synthesis, and protein translation. Dysregulation of DHX33 has been observed in various human cancers. In this study, we identified a short DHX33 variant in cells. The short DHX33 (hereafter referred to as DHX33‐2) has only 534 amino acids, which completely matches the C‐terminal helicase domain of full‐length DHX33 (DHX33‐1). Different from DHX33‐1, which mainly localizes to the nucleus, DHX33‐2 preferentially localizes to the cytoplasm. Through protein immunoprecipitation and RNA‐ immunoprecipitation analysis, we found that DHX33‐2 interacts with DDX3, eIF3, hnRNPs, poly (A) binding protein, and a subset of mRNAs. Further RNA sequencing analysis showed that DHX33 binds to a subset of mRNAs important in cell proliferation. DHX33‐2 stimulates the translation for specific mRNAs. Our study for the first time demonstrates the function of a short DHX33 variant in protein translation. Abstract : A new variant of DHX33 was identified in this study. This new DHX33 variant promotes specific mRNA translation but shows a cell‐type dependent expression pattern.